Development of microsatellites from Fothergilla ×intermedia (Hamamelidaceae) and cross transfer to four other genera within Hamamelidaceae1. (7th April 2015) - Hatmaker, E. Anne; Wadl, Phillip A.; Mantooth, Kristie; Scheffler, Brian E.; Ownley, Bonnie H.; Trigiano, Robert N.
Abstract : Premise of the study: We developed microsatellites from Fothergilla × intermedia to establish loci capable of distinguishing species and cultivars, and to assess genetic diversity for use by ornamental breeders and to transfer within Hamamelidaceae. Methods and Results: We sequenced a small insert genomic library enriched for microsatellites to develop 12 polymorphic microsatellite loci. The number of alleles detected ranged from four to 15 across five genera within Hamamelidaceae. Shannon's information index ranged from 0.07 to 0.14. Conclusions: These microsatellite loci provide a set of markers to evaluate genetic diversity of natural and cultivated collections and assist ornamental plant breeders for genetic studies of five popular genera of woody ornamental plants.